The Citizen Archive and Strategic Silencing: A Study on Rohingya Genocide - Abdulla Al Mahmud (History Studies)
This paper critically examines the role of citizen archives in the systemic disenfranchisement and eventual genocide of the Rohingya people in Myanmar. By analyzing the historical and contemporary practices of documenting national identity, it reveals how the Myanmar government's manipulation of citizen archives rendered the Rohingya stateless and silenced, culminating in the brutal ethnic cleansing recognized by the international community. The study juxtaposes this with similar archival strategies in the USA, UK, Palestine, and India, highlighting a disturbing trend where state-controlled identity documents are weaponized to discriminate against and control marginalized groups. The findings underscore an urgent need to monitor and reform the management of citizen archives to protect minority rights and prevent such atrocities, offering a poignant reminder of the dangers of allowing governmental control over personal identities to go unchecked.